Thermal and chemical structure of ethanol and 2-ethylhexanoic acid/ethanol SpraySyn flames - Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Nanoparticle synthesis; Flame spray pyrolysis; SpraySyn burner; Flame structure; Species distribution; Temperature distribution

Low Temperature Laser Sintering on a Standard System: First Attempts and Results with PA12 - Menge, Dennis; Schmid, Hans-Joachim
The laser sintering process has been a well-established AM process for many years. Disadvantages of LS are the low material variety and the thermal damage of the unprocessed material. The low temperature laser sintering attacks at this point and processes powder material at a build chamber temperature lower than the recrystallization temperature. This drastic reduction in temperature results in significantly less thermal damage to the material. This work deals with the low temperature laser sintering of Polyamide 12 (PA12) on a commercial, unmodified laser sintering system to compare it to standard laser sintered PA12 and to create the basis for low temperature laser sintering of high temperature materials on such a system. First results by changing the exposure parameters and by fixing parts on a building platform show a processing of PA12 on an EOS P396 at a build chamber temperature less than 100 °C instead of standard approx. 175 °C.
Keywords: Low Temp LS; Low Temperature Laser Sintering; Polyamid 12

Comparison and Validation of Irradiance Data: Satellite Meteorological Dataset MERRA-2 vs. Meteonorm and German Weather Service (DWD) - Khatibi, Arash; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
Access to precise meteorological data is crucial to be able to plan and install renewable energy systems such as solar power plants and wind farms. In case of solar energy, knowledge of local irradiance and air temperature values is very important. For this, various methods can be used such as installing local weather stations or using meteorological data from different organizations such as Meteonorm or official Deutscher Wetterdienst (DWD). An alternative is to use satellite reanalysis datasets provided by organizations like the National Aeronautics and Space Administration (NASA) and European Centre for Medium-Range Weather Forecasts (ECMWF). In this paper the “Modern-Era Retrospective analysis for Research and Applications” dataset version 2 (MERRA-2) will be presented, and its performance will be evaluated by comparing it to locally measured datasets provided by Meteonorm and DWD. The analysis shows very high correlation between MERRA-2 and local measurements (correlation coefficients of 0.99) for monthly global irradiance and air temperature values. The results prove the suitability of MERRA-2 data for applications requiring long historical data. Moreover, availability of MERRA-2 for the whole world with an acceptable resolution makes it a very valuable dataset.
Keywords: Energy potential estimation; Photovoltaic; Solar radiation; Temperature measurement; Satellite data; Meteonorm; MERRA-2; DWD

End Group Stability of Atom Transfer Radical Polymerization (ATRP)-Synthesized Poly(N-isopropylacrylamide): Perspectives for Diblock Copolymer Synthesis - Herberg, Artjom; Yu, Xiaoqian; Kuckling, Dirk (Polymers)
Keywords: controlled radical polymerization; atom transfer radical polymerization; end group determination; N-isopropylacrylamide; block copolymerization; smart polymers; temperature sensitive polymers; lower critical solution temperature; ESI-TOF mass spectrometry; ion mobility separation; size exclusion chromatography

Identification of temperature-dependent model parameters of ultrasonic piezo-composite transducers - Webersen, Manuel; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (AMA Conferences 2015)
When performing measurements, the effects of the measurement system itself on the measured data generally must be eliminated. Consequently, those effects, i.e. the system’s dynamic behavior, need to be known. For the piezo-composite transducers in an ultrasonic transmission line, a model based approach is used to describe their dynamic behavior and take into account its dependence on the environment temperature and the acoustic impedance of the target medium. Temperature-dependent model parameters are presented, which are obtained by performing a multiplepart identification process on the transducer model, based on electrical impedance measurements [1]. The identification process uses an inverse approach for optimizing a subset of the model parameters. Additionally, algorithmic differentiation methods are used to determine accurate derivatives. In a final optimization step, impedance measurements taken at different temperatures are used to determine the temperature dependencies of the model parameters. These can then be used to assess the plausibility of the identification results. Additionally, the parameters can be expressed as polynomials in the temperature to take different operating conditions into account.
Keywords: piezo-composite; transducer; temperature dependency; identification; plausibility

Thermo-Mechanical Model for Wheel Rail Contact using Coupled Point Contact Elements - Neuhaus, Jan; Sextro, Walter (Proceedings of the 5th International Conference on Computational Methods)
A model to calculate the locally resolved tangential contact forces of the wheel rail contact with respect to contact kinematics, material and surface properties as well as temperature is introduced. The elasticity of wheel and rail is modeled as an elastic layer consisting of point contact elements connected by springs to each other and to the wheel. Each element has two degrees of freedom in tangential directions. The resulting total stiffness matrix is reduced to calculate only the position of the elements in contact. Friction forces as well as contact stiffnesses are incorporated by a nonlinear force-displacement characteristic, which originates from a detailed contact model. The contact elements are transported through the contact zone in discrete time steps. After each time step an equilibrium is calculated. For all elements, their temperature and its influence on local friction are regarded by calculating friction power and temperature each time step.
Keywords: Rolling Contact; Discrete Elements; Contact Stiffness; Temperature

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

Friction in wheel--rail contact: A model comprising interfacial fluids, surface roughness and temperature - Tomberger, Christoph; Dietmaier, Peter; Sextro, Walter; Six, Klaus (Wear)
A profound description of friction in wheel--rail contact plays an essential role for optimization of traction control strategies, as input quantity for railway simulations in general and for the estimation of wear and rolling contact fatigue. A multitude of wheel--rail contact models exists, however, traction--creepage curves obtained from measurements show quantitative and qualitative deviations. There are several phenomena which influence the traction--creepage characteristics: Mechanisms resulting from surface roughness, frictional heating or the presence of interfacial fluids can have a dominating influence on friction. In this paper, a new wheel--rail contact model, accounting for these influential parameters, will be presented. The presented model accounts for the interaction of an interfacial fluid model for combined boundary and mixed lubrication of rough surfaces with a wheel--rail contact model that additionally accounts for frictional heating. A quantitative comparison with measurements found in the literature is not conducted, since the exact conditions of the measurements are mostly unknown and parameters can easily be adjusted to fit the measurements. Emphasis is placed on the qualitative behavior of the model with respect to the measurements and good agreement is found. The dependence of the maximum traction coefficient on rolling velocity, surface roughness and normal load is studied under dry and water lubricated conditions.
Keywords: Wheel--rail contact; Rolling contact; Friction; Interfacial fluid; Lubrication; Surface roughness; Contact temperature

Ultrasonic Transducer for the Hydrothermal Method - Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Ageba, Ryo; Kadota, Yoishi; Morita, Takeshi (Journal of Korean Physical Society)
Direct ultrasound irradiation is advantageous to increase the efficiency of the hydrothermal method which can be used for the production of piezoelectric thin films and lead free piezoelectric ceramics. To apply ultrasound directly to the process transducer prototypes were developed regarding the boundary conditions of the hydrothermal method. LiNbO$_{3}$ and PIC 181 were proven as feasible materials for high temperature resistant transducers ($≥ 200^° C$). Resistance of the transducers horn against the corrosive mineralizer was achieved by using Hastelloy C-22. The efficiency of the ultrasound assisted hydrothermal method depends on the generated sound field. Impedance and sound field measurements have shown that the sound field depends on the filling level and the position and design of the transducer.
Keywords: High-temperature transducer; Hydrothermal method; Lithium-niobate transducer

Profile Processing and Evolution for Smart Environments - Schäfer, Robbie; Müller, Wolfgang; Groppe, Jinghua (Proceedings of the 3rd International Conference on Ubiquitous Intelligence and Computing (UIC-06))
Ubiquitous systems use context information to select and adapt multimodal user interfaces and appliances for individual users in certain situations. However, in order to enable true reactive environments, context information has to be adequately collected, filtered, and processed and combined with user, device and other profiles. In this article, we present how an XML-based transcoding system can be applied for advanced profile processing and evolution. We demonstrate how to encode domain knowledge into sets of rules, which perform adaptations of user, device and context profiles for smart environments.
Keywords: Resource Description Framework User Preference Smart Home Prefer Temperature Preference Profile